Peran Sociopreneur dalam Transformasi Sosial dan Pengentasan Kemiskinan Melalui Lembaga Keuangan Mikro Perspektif Sosiologi dan Antropologi - Nailus Sakinah, Nailus Sakinah; Arifin, Tajul; Abdal, Abdal (Strata Social and Humanities Studies, 2023)
This article discusses social transformation and poverty alleviation, these are the two main challenges in community development. The role of the socialpreneur, who is a social entrepreneur, has great potential in creating positive change in the context. Socialpreneurs can play a role in overcoming poverty problems through microfinance institutions. Socialpreneurs can use innovation, creativity, entrepreneurial spirit to identify pressing social problems and find sustainable solutions. The author uses qualitative methods, with secondary data analysis, sourced from books, journals and articles related to this discussion. The results of his research stated that poverty is a serious problem that endangers scarcity, health and education. Islam encourages its followers to avoid poverty, and Islamic microfinance institutions are effective in reducing poverty. The integration of social entrepreneurship in microfinance institutions helps maintain a balance between profitability and social impact. Measures such as poverty-focused services and business training support social transformation and poverty alleviation. Socialpreneurship allows individuals to run a business while contributing to social change. The millennial generation views this as a way to achieve Sustainable Development Goals (SDGs). In efforts to eradicate poverty through socialpreneurship, sociological and anthropological perspectives help understand cultural values, social interactions, and the influence of stigmatization on poor communities.